EFFECTS OF LASER DRILLING ON MECHANICAL PROPERTIES AND IMPREGNABILITY OF FIR AND SPRUCE WOOD* (Innovation in Woodworking Industry and Engineering design, 2026)
Fir (Abies borisii regis) and spruce (Picea excelsa) wood specimens, 2 × 2 cm in cross section and 34 cm long, were prepared with true radial and tangential surfaces. All lateral surfaces of the specimens were drilled by laser to a depth of 4 mm (1/5 of specimen thickness) with two drilling patterns (distance between holes 1 × 1 cm and 1 × 2 cm). ). After drilling, the mechanical strength of wood (MOE, MOR, axial compression, toughness) was determined and compared with non-drilled controls. MOE was not affected by the laser drilling, MOR was significantly increased, axial compression was increased and toughness was decreased but not significantly. The overall results imply that strength properties do not decline by the laser drilling. Furthermore, wood specimens were impregnated with rape oil and CCB preservatives by applying vacuum (0.6 mmHg) and pressure (1,5 bars) for 15 minutes and 30 minutes, respectively. The results showed that both drilling patterns improved the retention and penetration of preservatives in fir and spruce wood specimens and, thus, are encouraging for further evaluating the drilling effects on the liquid permeability of these refractory to impregnation species. This effect was more pronounced in fir than in spruce wood.